2021
DOI: 10.3390/electronics10182289
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Evaluation of a Micro-Coaxial Antenna Set to Treat Bone Tumors: Design, Parametric FEM Modeling and Evaluation in Multilayer Phantom and Ex Vivo Porcine Tissue

Abstract: Bone cancer is rare in adults, the most affected persons by this disease are young people and children. The common treatments for bone cancer are surgery, chemotherapy, and targeted therapies; however, all of them have side-effects that decrease the patient’s quality of life. Thermotherapy is one of the most promising treatments for bone cancer; its main goal is to increase the tumor temperature to kill cancerous cells. Although some micro-coaxial antennas have been used to treat bone tumors, most of them are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…The evaluation was based on SWR analysis, tissue volume at ablation temperatures, maximum reached temperatures, and isothermal contours. The double slot (DS) and the monopole (MTM) antennas were chosen to form the arrays, as they were previously designed and tested [ 17 ], i.e., their correct performance has been evaluated by experimentation in phantom and porcine ex vivo tissue. Previous experimental tests showed that both antennas could generate ablation temperatures at bone using 10 W of input power applied for durations between 5 and 10 min.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The evaluation was based on SWR analysis, tissue volume at ablation temperatures, maximum reached temperatures, and isothermal contours. The double slot (DS) and the monopole (MTM) antennas were chosen to form the arrays, as they were previously designed and tested [ 17 ], i.e., their correct performance has been evaluated by experimentation in phantom and porcine ex vivo tissue. Previous experimental tests showed that both antennas could generate ablation temperatures at bone using 10 W of input power applied for durations between 5 and 10 min.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, as this research was focus on bone tumors, the monopole antenna was also proposed to evaluate the possibility to cover a larger region of bone tissue. The double slot and the monopole antennas were previously modeled, optimized, and tested in multi-tissue phantoms and ex vivo porcine tissue by this research group [ 17 ]. The computational models showed SWR values of 1.26 and 1.55 for the double slot (DS) and the monopole (MTM) antennas, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations